Faktor-Faktor yang Berhubungan dengan Masalah Gizi Lebih pada Guru Sekolah Menengah Atas di Kota Bogor: Factors Related to Overnutrition among High School Teachers in Bogor City - Lende, Lizbeth Maureen Regina; Wahyuningsih, Utami; Marjan, Avliya Quratul (Amerta Nutrition, 2024)
Background: Teachers play a vital role in education and must maintain productivity. However, some teachers face overnutrition due to spending most of their working hours on low-physical-activity tasks. Previous research in vocational high schools (SMK) in Bogor City reported that 37.3% of teachers were classified as having level I obesity, while 10.7% had level II obesity. Objectives: This study aims to examine factors associated with overnutrition among senior high school (SMA) teachers in Bogor City and to analyze differences in overnutrition risk factors between public and private schools. Methods: A cross-sectional design with a total sampling method was employed, involving 121 teachers, comprising 60 from public schools and 61 from private schools. Data collection included questionnaires and anthropometric measurements, analyzed using Chi-Square and Mann-Whitney tests. Results: The analysis revealed significant associations between overnutrition and factors such as age (p-value<0.05), family income (p-value<0.05), physical activity (p-value<0.05), energy intake (p-value<0.001), protein intake (p-value<0.001), fat intake (p-value<0.001), carbohydrate intake (p-value<0.001), and nutritional knowledge (p-value<0.001). Gender, vegetable and fruit consumption, and stress (p-value>0.05) showed no association. Significant differences were found in physical activity (p-value<0.05), stress (p-value<0.05), protein intake (p-value<0.05), fat intake (p-value<0.05), carbohydrate intake (p-value<0.05), and vegetable (p-value<0.001) and fruit (p-value<0.001) consumption between public and private school teachers. Conclusions: Factors associated with overnutrition among high school teachers in Bogor City include age, physical activity, dietary intake (energy, protein, fat, and carbohydrates), nutritional knowledge, and family income, with significant differences between public and private schools.